Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1016/j.celrep.2015.04.065
|View full text |Cite
|
Sign up to set email alerts
|

The eIF4E-Binding Protein 4E-T Is a Component of the mRNA Decay Machinery that Bridges the 5′ and 3′ Termini of Target mRNAs

Abstract: Eukaryotic mRNA degradation often initiates with the recruitment of the CCR4-NOT deadenylase complex and decay factors to the mRNA 3' terminus. How the 3'-proximal decay machinery interacts with the 5'-terminal cap structure in order to engender mRNA decapping and 5'-3' degradation is unclear. Human 4E-T is an eIF4E-binding protein that has been reported to promote mRNA decay, albeit via an unknown mechanism. Here, we show that 4E-T is a component of the mRNA decay machinery and interacts with factors includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
94
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(104 citation statements)
references
References 44 publications
8
94
1
Order By: Relevance
“…It was recently reported that 4E-T is recruited to mRNAs targeted by CCR4-NOT and that 4E-T functions as an important cofactor of the mRNA decay machinery (13). This finding raises the intriguing possibility that 4E-T may play a dual role in miRNA-mediated silencing: interaction of 4E-T with 4EHP potentiates translation repression, whereas its direct binding to eIF4E enables mRNA decay.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was recently reported that 4E-T is recruited to mRNAs targeted by CCR4-NOT and that 4E-T functions as an important cofactor of the mRNA decay machinery (13). This finding raises the intriguing possibility that 4E-T may play a dual role in miRNA-mediated silencing: interaction of 4E-T with 4EHP potentiates translation repression, whereas its direct binding to eIF4E enables mRNA decay.…”
Section: Discussionmentioning
confidence: 99%
“…The silencing activity of miRISC is mediated by the CCR4-NOT deadenylase complex through the scaffolding subunit, CNOT1 (6)(7)(8). CNOT1 recruits the DDX6 and 4E-T (eIF4E transporter, also known as EIF4ENIF1) proteins, which are important for miRNA-mediated silencing (9)(10)(11)(12)(13)(14)(15)(16). The 4E-T protein is a conserved eIF4E-binding protein, which directly binds to the dorsal surface of eIF4E through its canonical eIF4E-binding YX 4 LL (Y 30 TKEELL) motif and impairs the eIF4E/eIF4G interaction and translation initiation (17).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, we found that DDX6‐mediated repression does not require ribosomal scanning, suggesting that DDX6 may interfere with eIF4E or eIF4G function. In this context, it has been shown that DDX6 interacts with the eIF4E‐transporter protein (4E‐T; Nishimura et al , 2015; Ozgur et al , 2015), an eIF4E‐binding protein that competes with eIF4G for binding to eIF4E and represses translation initiation. However, depletion of 4E‐T only partially alleviates silencing (this study; Kamenska et al , 2014; Nishimura et al , 2015), which implies that DDX6 may employ additional mechanisms to repress translation that are thus far unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Supporting these results, structural studies showed that CNOT1 directly interacts with DDX6 through the MIF4G domain [45,46,61]. A recent study demonstrated that in humans the eIF4E-binding protein 4E-T interacts with CNOT1 and a number of decapping activators, including PATL1, LSM14, DDX6, LSM2, and DCP1 by using a combination of coimmunoprecipitation and proximal biotinylation (Bio-ID) techniques [55]. They showed that 4E-T promotes miRNA-mediated mRNA decay through the eIF4E-binding domain, suggesting that 4E-T bridges the 3 0 -terminal mRNA decay complex to the 5 0 m 7 G-cap via binding to eIF4E [55].…”
mentioning
confidence: 80%